Post core restoration after an endodontic treatment - Slamet Soetanto (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2005)
Disorder after an endodontic treatment of the crown portion of a tooth, needs efforts to restore its function and aesthetic. To support the intention for a restoration, a strengthener and an optimal retention in the root canal become necessary. A strengthener in the root canal is a fabricated dowel which can be directly applied. This technique has been developed by using a fiber substance. A restoration as an effort to return the function of mastication, can also suffer a failure. With a right design, among others the posthole preparation, post-choosing, and the core design, any unfavorable situation can be limited.